Numerical Simulation of Quantum Logic Gates Based on Quantum Wires. Issue 1 (2001) - Bertoni, A.; Bordone, P.; Brunetti, R.; Jacoboni, C.; Reggiani, S.
Abstract : A system based on frontier mesoscopic semiconductor technology, able to perform the basic quantum operations needed for quantum computation, is proposed. The elementary quantum bit (qubit) is defined as the state of an electron running along a couple of quantum wires coupled through a potential barrier with variable height and/ or width. A proper design of the system, together with the action of Coulomb interaction of two electrons representing two different qubits, allows the implementation of basic one-qubit and two-qubit quantum logic gates. Numerical simulations confirm the correctness of the hypothesis.